Vaginal Douching, Condom Use, and Sexually Transmitted Infections Among Chinese Female Sex Workers - WANG, BO (2005)
BACKGROUND AND OBJECTIVE: Vaginal douching has been hypothesized to increase a woman’s risk for human immunodeficiency virus (HIV) infection. However, data on the prevalence of this practice and its association with condom use and sexually transmitted infections (STIs) are limited. STUDY: A cross-sectional survey among 454 female sex workers (FSWs) in a Chinese county. RESULTS: Vaginal douching was reported by 64.7% of the women. The prevalence of self-reported history of STI and that of current STI was 19.4% and 41.5%, respectively. Fifteen percent of the women reported consistent use of condoms with their clients and 8.4% with their regular partners. Vaginal douching was significantly associated with decreased use of condoms (with clients: OR = 0.31; with regular partner(s): OR = 0.22) and increased rate of self-reported STI history (OR = 1.95). However, there was no direct relation between douching and current STI. Over one third of the women believed that douching can prevent STI/HIV. CONCLUSION: Vaginal douching exposes FSWs to a high risk of STI/HIV. Medical professional and public health workers should correct women’s misconception about the effectiveness of douching and discourage women from douching through educational activities.